Incapacidades em vítimas graves de acidentes de trânsito, Cuiabá - Mato Grosso, 2018 - Andrade, Kelly Cristina Teixeira Brandão de (2019)
Traffic accidents have been prominent due to injuries due to non-fatal events, which can have lifelong effects such as disabilities. The morbidity and mortality indicators point to a still limited knowledge about the magnitude of the sequelae of traffic accidents, providing neither information on the prevalence of disability nor the impact they have on people's lives. Objective: Analyze the evolution of disability in serious victims of traffic accidents admitted to a public reference hospital for trauma care in Cuiabá-Mato Grosso. Method: Prospective longitudinal study based on medical record data and interviews with 67 serious traffic accident victims admitted to the Cuiabá Municipal Emergency Room Hospital in June 2018. Three observations were made between June 2018 and February 2019. , in which a data collection instrument based on the Cheklist of the International Classification of Functioning, Disability and Health (ICF) was applied. The outcome variable “disability” was determined and correlated with sociodemographic and accident-related variables. Absolute and relative frequencies were calculated in the descriptive analysis, and in the bivariate analysis the Fisher's exact test was used. Prevalence, Prevalence Ratio (PR) with their respective Confidence Intervals (95% CI) and p-value were estimated. Results: Predominated male victims (71.6%), between 20 to 39 years (58.2%), black / brown (82.1%) and motorcyclists (91.0%); About 33.0% of motorcycle drivers had no license and 54.4% of accidents were work related. About six months after the accident, most individuals remained with impaired sensory functions and pain (80.6%), musculoskeletal and movement-related (74.6%); and movement-related body structure deficiencies (76.1%). Activity limitations and participation restrictions were predominantly related to mobility (82.1%). The presence of barriers in services, systems and policies was the main obstacle faced, still present for 62.7% of individuals at the end of the study. At the end of the observation 94.0% of the individuals remained with some disability and 79.1% with disability, the latter being of moderate extension to half of these individuals. No statistical significance was found in the analysis between disability and independent variables.Conclusion: The study showed the magnitude and extent of disabilities and disabilities in severe traffic accident victims, showing that there are multiple injuries, which change over time in the domains and their categories, and especially in the extent of these. affecting people's lives in different ways, leading to serious social and economic problems.